Different evasion strategies in multiple myeloma - Wang, Chaofan; Wang, Wanting; Wang, Moran; Deng, Jun; Sun, Chunyan; Hu, Yu; Luo, Shanshan (Frontiers in Immunology, 2024)
Multiple myeloma is the second most common malignant hematologic malignancy，which evolved different strategies for immune escape from the host immune surveillance and drug resistance, including uncontrolled proliferation of malignant plasma cells in the bone marrow, genetic mutations, or deletion of tumor antigens to escape from special targets and so. Therefore, it is a big challenge to efficiently treat multiple myeloma patients. Despite recent applications of immunomodulatory drugs (IMiDS), protease inhibitors (PI), targeted monoclonal antibodies (mAb), and even hematopoietic stem cell transplantation (HSCT), it remains hardly curable. Summarizing the possible evasion strategies can help design specific drugs for multiple myeloma treatment. This review aims to provide an integrative overview of the intrinsic and extrinsic evasion mechanisms as well as recently discovered microbiota utilized by multiple myeloma for immune evasion and drug resistance, hopefully providing a theoretical basis for the rational design of specific immunotherapies or drug combinations to prevent the uncontrolled proliferation of MM, overcome drug resistance and improve patient survival.